Bihar’s Poorest Women Are Changing Their Lives: A Case study of Bihar Rural Livelihoods Promotion Society (JEEViKA): Transforming lives of rural women through empowerment and entrepreneurship (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Rural women undertake multiple tasks on daily basis to secure their lives and their families. Women play a critical role in family economy and also ensure domestic duties. Women once empowered by working together in Self-Help Group and micro-credit groups have shown they can slowly but surely break free from age-old discrimination and total economic dependence, gain respect, voice their opinions, manage their own micro- enterprises and revitalize their villages.The paper seeks to study how Bihar Rural Livelihood Promotion Society (JEEViKA) has successfully made an attempt to change the lives of the rural women. It is an initiative to scale up women’s empowerment in the one of the poorest regions of India to bring transformational change to the lives of rural women, their families, economy and society.‘JEEViKA’ which means livelihood, started in 2007 and continued into a second phase in 2016, focussed on creating self-help groups for women to provide them with access to small enterprise funding, services, and public entitlements. It has had huge impact on social, economic and political empowerment of rural women as all the three are interlinked. However, challenges are also many and much needs to be done.